Religious Tourism at Mama Sempur's Tomb Improves the Quality of Economic Welfare with Religious Tourism - Amirudin, Muhammad; Rahman, Mohammad Taufiq (Jurnal Iman dan Spiritualitas, 2026)
This study aims to analyze the impact of religious tourism at Makam Mama Sempur on the economic well-being of the local community and how social and economic transformations occur due to the increasing number of pilgrims. Employing a qualitative research approach with a descriptive-analytical method and field study, this research explores the dynamics of community-based economic shifts. The findings reveal that religious tourism has created new economic opportunities, allowing residents to transition from precarious employment to entrepreneurship, thereby improving their standard of living. Drawing on microeconomic and socio-economic theories, the study highlights that the sustainability of this sector depends on social capital and the implementation of inclusive management strategies. The study concludes that religious tourism serves not only as a spiritual practice but also as a catalyst for local economic growth. However, its sustainability requires careful attention to environmental management and the equitable distribution of economic benefits.